Study of the determinants of chronic malnutrition in northern Nigeria: Quantitative evidence from the Nigeria Demographic and Health Surveys - Amare, Mulubrhan; Benson, Todd; Fadare, Olusegun; Oyeyemi, Motunrayo (International Food Policy Research Institute, 2017)
To better understand the drivers of chronic child undernutrition in northern Nigeria and how those drivers differ from other areas of the country, this paper presents the results of an econometric analysis of data from the 2008 and 2013 Nigeria Demographic and Health Surveys. A standard child-level regression based approach is used for the first part of the analysis using as the dependent variable whether the child aged 6 to 23 months is stunted (height-for-age z-score (HAZ) < -2.0). Separate models of the drivers of child stunting are developed for northern Nigeria (Northwest and Northeast geopolitical zones) in 2008 and in 2013 and for other areas of Nigeria in 2013. The analysis then is extended by comparing the model for northern Nigeria in 2013 to other areas of Nigeria in 2013 to decompose differences between the models. This was done to gain understanding on how the determinants of child stunting in children aged 6 to 23 months differ between the two areas to better understand how well successful approaches used elsewhere in Nigeria to reduce child stunting might work in northern Nigeria.